2006
DOI: 10.1159/000097008
|View full text |Cite
|
Sign up to set email alerts
|

Two Patients with Tremor Caused by Cortical Lesions

Abstract: Myoclonic tremor due to cortical lesions is a rare condition and must be distinguished from other causes of tremor. This is because the treatment strategies of tremor may differ due to the various etiologies. We present here two cases with myoclonic tremor caused by parietal cortical lesions showing tremulous finger movement provoked by action and posture. Clinical and electrophysiological features of the patients were reported and compared with the features of the patients with cortical tremor in association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Rubral and palatal tremor may respond to clonazepam and sodium valproate [63]. Ondo et al ., [64] illustrated a case about two patients with myoclonic tremor induced by parietal cortical lesions with tremulous finger movements induce by action and posture and had been successfully treated with both clonazepam and sodium valproate as first-line agents for orthostatic tremor [62]. Dystonic tremor is treated as dystonia [see above].…”
Section: Tremormentioning
confidence: 99%
“…Rubral and palatal tremor may respond to clonazepam and sodium valproate [63]. Ondo et al ., [64] illustrated a case about two patients with myoclonic tremor induced by parietal cortical lesions with tremulous finger movements induce by action and posture and had been successfully treated with both clonazepam and sodium valproate as first-line agents for orthostatic tremor [62]. Dystonic tremor is treated as dystonia [see above].…”
Section: Tremormentioning
confidence: 99%
“…Lesions in different anatomical locations of the cerebellar pathways result in different forms of postural tremor [12]. Acute or subacute postural tremor may result from supra-tentorial cortical lesions such as mass occupying lesions, ischemic lesions and arterio-venous malformations [13]. Postural tremor of the upper limbs is also a common manifestation of Wilson's disease, very likely generated within a synchronized cerebello-thalamo-cortical network [14].…”
Section: Principal Human Disorders Associated With Each Category Of Tmentioning
confidence: 99%
“…Two cases were presented with the myoclonic tremor caused by parietal cortical lesions manifesting tremulous finger movement provoked by action and posture. The tremor responded well to valproate and clonazepam (8). In 2011 Andreas Puschmann et al reported that progress was achieved in understanding the patophysiology of tremor and that available options for the treatment of tremor in patients have increased.…”
Section: Discussionmentioning
confidence: 99%